2002
DOI: 10.1074/jbc.m207100200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acidic Residues in the Extracellular Loops of the Seven-transmembrane Domain of the Human Ca2+ Receptor Critical for Response to Ca2+ and a Positive Allosteric Modulator

Abstract: We investigated the role of the eight acidic residues in the extracellular loops (exo-loops) of the seven-transmembrane domain of the human Ca 2؉ receptor (hCaR) in receptor activation by Ca 2؉ and in response to a positive allosteric modulator, NPS R-568. Both in the context of the full-length receptor and of a truncated receptor lacking the extracellular domain (Rho-C-hCaR), we mutated each acidic residue to alanine, singly and in combination, and tested the effect on expression of the receptor, on activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 30 publications
5
44
1
Order By: Relevance
“…No attempt was made to model the CaSR in its activated form bound to Calindol or NPS R-568, because of the lack of an adequate three-dimensional template (33). However, our data emphasizes the crucial role of Glu-837 in anchoring NPS R-568, as previously observed (17,19), and of Calindol, presumably through a salt bridge with the protonated secondary amine of the two compounds as we previously proposed for the calcilytics. Our study also underscores the role of Ile-841 in anchoring the two calcimimetics as indicated by the lack of Ca 2ϩ potentiation of IP response by both compounds in the mutants.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…No attempt was made to model the CaSR in its activated form bound to Calindol or NPS R-568, because of the lack of an adequate three-dimensional template (33). However, our data emphasizes the crucial role of Glu-837 in anchoring NPS R-568, as previously observed (17,19), and of Calindol, presumably through a salt bridge with the protonated secondary amine of the two compounds as we previously proposed for the calcilytics. Our study also underscores the role of Ile-841 in anchoring the two calcimimetics as indicated by the lack of Ca 2ϩ potentiation of IP response by both compounds in the mutants.…”
Section: Discussionsupporting
confidence: 55%
“…The subsequent conformational change that presumably occurs throughout the cysteine-rich region affects the seven TM regions leading to receptor activation. Interestingly, three acidic residues located in the extracellular loop 2 of the CaSR have been demonstrated to maintain an inactive conformation of the seven TM regions, further highlighting the complex processes of CaSR activation (17). However, the precise molecular mechanisms involved in such activation are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Headless CaR Construct-A headless CaR deletion mutant elsewhere referred to as Rho-C-CaR (9 -11) or T903-Rhoc (12) containing 20 amino acids of the N terminus of rhodopsin and amino acids 600 -903 of the hCaR was constructed in pcDNA3.1 using PCR as described previously (9,11). Briefly, the sense primer was 100 nucleotides long, corresponding to the nucleotide sequence of the N-terminal 20-amino acid signal peptide of bovine rhodopsin and nucleotide positions 1797-1832 of the hCaR (GenBank TM 20759).…”
Section: Methodsmentioning
confidence: 99%
“…Position 3.36 has also been shown to play a pivotal role in antagonist binding to several different GPCRs. Last, Glu-837 7.39 is a key residue of various unrelated GPCRs for anchoring competitive antagonists and is implicated in the recognition of a reference calcimimetic in the CaSR (21). Our results concerning the E837A mutant are in agreement with those obtained by Hu et al (21) showing that this mutant is expressed at levels comparable to those of the WT receptor when transfected in HEK293 cells, and its sensitivity to Ca 2ϩ is not altered despite a lower maximal response.…”
Section: Functional Analysis Of Calhex 231 Inhibition Of Mutants Locamentioning
confidence: 99%